Motif Penggunaan Second Account Instagram Mahasiswa di Kota Bandung - Syaefulloh , Iqbal (Jurnal Ilmu Komunikasi, 2023)
This research aims to describe the motives for using second accounts on Instagram social media by generation Z students in the city of Bandung. The method used in this research is descriptive qualitative. The research results show that the motives for using second Instagram accounts among generation Z students are generally divided into two; First, students separate personal interests from business. Second, students want to separate formal and informal life on Instagram social media. The second motive is very dominant for generation Z. This is because they limit the quality and quantity of sharing moments on Instagram so that their personal data cannot be accessed by anyone. In addition, they also divide their friendship circles to avoid potential bias in communicating on Instagram social media. They are less confident if all these shares are on one account, so the audience on Instagram social media will be confused about that person's personality.